Effect of pre-crops on the inoculum potential of arbuscular mycorrhizal fungi and cassava yield - Souza, Francisco Adrino de; Trufem, Sandra Farto Botelho; Almeida, Dejair Lopes de; Silva, Eliane Maria Ribeiro da; Guerra, José Guilherme Marinho (Pesquisa Agropecuaria Brasileira, 1999)
The effect of pre-crops on the inoculum potential (IP) of arbuscular mycorrhizal fungi (AMF) and yield of cassava was evaluated on a Red-Yellow Podzolic soil in the field. The experiment was carried out at Embrapa-Centro Nacional de Pesquisa de Agrobiologia (CNPAB), Seropédica, RJ, Brazil, in plots with 30 m2 arranged in a randomised block design with four replications. As pre-crops, four legume species were used: Canavalia ensiformis, Mucuna aterrina, Crotalaria juncea and Cajanus cajan; and a grass Sorghum bicolor (BR 005) in relation to plots, without plants. After a grow period of 82 days, at the same plots, cassava stakes were planted, which were grown for eight months. The yield of cassava roots ranged from 12.76 to 17.20 ton ha-1, although no statistical significant effects were found between the treatments. There were 16 AMF species identified, and some of them had a significant frequency changement after the growing cycles. The number of infective propagules were significantly increased after sorghum crop in relation to plots without plants. It was showed that identification of plant species capable to increase the IP in the field soils may be a good alternative way to solve the problem of inoculum production to mycotrophic crops in the field.
Keywords: Manihot esculenta; Canavalia ensiformis; Mucuna aterrima; Crotalaria juncea; Cajanus cajan; Sorghum bicolor; infective propagule; number of spores